Drawing in the creative and pedagogical activities of Viktor Bystryakov - Budnyk, Andriy; Konoval, Viktor; Solovei, Oles; Pylypenko, Ivan (Art and Design, 2026)
The relevance of this work lied in the absence of a thorough analysis of Viktor Bystryakov’s easel graphics, despite its significance for understanding the development of the Ukrainian school of drawing in the second half of the 20 th century. The aim of the study was to examine and analyse the legacy of Ukrainian artist and teacher Viktor Bystryakov in the field of drawing. Comparative and historical methods, methods of art analysis and empirical research were used. The article identified the distinctive features of drawing in the work of the Ukrainian artist, who used and continued the realistic traditions of the Kyiv school of drawing. The patterns of the master’s work were characterised, such as: generalisation of form, subordination of the secondary to the main, compositional balance, perfect mastery of line and spot, skilful use of the technical features of the graphic materials used and the base on which the drawing is applied. The study found that Viktor Bystryakov’s individual style of drawing was influenced by the methodological approaches of S. Podervianskyi, O. Kryvonos, and T. Yablonska. The article analysed Viktor Bystryakov’s pedagogical approaches, which have made a significant contribution to the development of Ukrainian artistic and educational practice. In the course of analysing scientific works devoted to the artist, it was established that his creative work is mainly covered in the context of exhibition activity and pedagogical practice. The main directions of the creative approach to the execution of easel drawings were identified on the basis of a newly discovered empirical research base, which consists of drawings found in the artist’s creative workshop and quotations from his archives, which are being published for the first time. The principles of easel drawing, confirmed by teaching practice, can be used in methodological materials in the educational process when training a wide range of specialists: designers, graphic artists, illustrators, motion designers and animation artists